Voltage Standing Wave Ratio as An Important Parameter for Resilient Communication - Andrzej FIRLEJ; Slawomir MUSIAL (Communications of International Proceedings, 2021)
The following article describes the voltage standing wave ratio VSWR parameter. The parameter is very important for resilient, efficient communication. It explains a physical meaning of VSWR. There is a presentation of mismatch effects and the way of calculating of VSWR. There are also presented the relationships between the voltage standing wave ratio VSWR and the standing wave ratio SWR. There is given an example of calculation: reflection coefficient, electrical length of the cable, wave velocity in the cable, VSWR and the amount of power from output of the transmitter absorbed by the antenna for given configuration. It is presented developed software to calculate these parameters. There is also explain necessity of impedance matching in microwave circuit. There are also presented the adverse effects of mismatch.
Keywords: voltage standing wave ratio; mismatch loss; wireless communication; reliability of communication